HUBUNGAN KUALITAS TIDUR DENGAN PENINGKATAN TEKANAN DARAH PADA LANSIA DI UNIT PELAYANAN SOSIAL LANJUT USIA PUCANG GADING KOTA SEMARANG - Ni Nyoman Maryaningtyas Adinatha; Indah Wulaningsih (Jurnal Surya Muda, 2019)
Hypertension is a degenerative disease. Generally blood pressure increases slowly with age. Insufficient quality and quantity of sleep can damage memory and cognitive abilities. If today continues for years, it will have an impact on high blood pressure. To determine the relationship between sleep quality and increased blood pressure in the elderly in the elderly service unit of Pucang Gading, Semarang City. This type of research is quantitative cross sectional design. Purposive sampling technique Research sample 48 respondents Chi-Square statistical test. Good sleep quality mostly had pre hypertension blood pressure as many as 14 respondents (63.6%) and those with poor sleep quality mostly had hypertension blood pressure as many as 19 respondents (73.1%). There is a relationship between sleep quality and elevated blood pressure in the elderly social care unit of Pucang Gading, Semarang City, with a p value of 0.000 <0.05.